Exposure Effect of Al-QuranMurattalon Spatial Memory on Albino Rat (Rattus novergicus) - Abdurrahman Afa Haridhi; Nanang Wiyono; Yunia Hastami; Muthmainah Muthmainah (Nexus Biomedika, 2017)
Introduction: Al Qur'an is Allah Subhanahuwataalas words which was sent as a miracle to Prophet Muhammad Sallallahualaihiwasallam as a guidance for mankind. Listening to Quran recitation (murattal) is known to increase the activity of alpha wave better than listening to classical music. In the previous study, listening to classical music is known to expand the spatial memory of albino rats. This study aimed to determine the effect of Al-Quran murattal exposure on albino rats (Rattus norvegicus)spatial memory.Methods: This experimental study was conducted in the Anatomy and Embryology Laboratory at FK UNS. A total of 14 male Wistar rats aged 14-21 days old were used as samples in this experiment.Samples were divided into control group (KK)and intervention group (KP) using randomized technique. KPwas exposed tomurattalaudio fromsurah Al-Baqarahby Syaikh Fahd Al-Kanderi through active speaker 12 hours/day for 28 days. The soundintensity ranged from 65-80dB was measured using sound level meter. The level of spatial memory was tested using Morris Water Maze test on the 29th to 33rdday. Probe test and sensorimotoric test was conducted on the 34th day. The resultthen analyzed with Independent t-Test and Mann Whitney (? = 0,05). Results: Spatial learning test shows average escape latency in KKand KP on the 1st dayat 35.55 and 33.20 seconds (s) respectively(p = 0.545), 2nd day (20.67s and 20.75s, p = 0.989), 3rd day (12.32s and 11.83s, p = 1.000), 4th day (15.78s and 10.37s, p = 0.036), 5th day (10.85s and 13.75s, p = 0,567). The probe test showed a significant difference (13,12s and 17.27s, p = 0,012) and sensorimotoric test did not show any significant difference (5.71s and 6.00s, p = 0,823). Conclusion: The Probe Test result indicated that Al-Quran murattal exposure increases the Spatial Memory persistence in Rats (Rattus norvegicus). Keywords: murattal Al-Quran, spatial memory, Morris Water Maze